2020
DOI: 10.1186/s13638-020-01826-x
|View full text |Cite
|
Sign up to set email alerts
|

Object detection in real time based on improved single shot multi-box detector algorithm

Abstract: In today’s scenario, the fastest algorithm which uses a single layer of convolutional network to detect the objects from the image is single shot multi-box detector (SSD) algorithm. This paper studies object detection techniques to detect objects in real time on any device running the proposed model in any environment. In this paper, we have increased the classification accuracy of detecting objects by improving the SSD algorithm while keeping the speed constant. These improvements have been done in their conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…YOLOv3 is an improved version of YOLOv2, featuring a new feature extraction network, a better backbone classifier, and multiscale prediction. Although Kumar et al [12] suggested a two-stage detector with high object detection accuracy, it is limited for video surveillance due to sluggish real-time inference speed. Although Morera et al [13] suggested YOLOv3, it achieved the same classification accuracy as a single-shot detector (SSD).…”
Section: Literature Reviewmentioning
confidence: 99%
“…YOLOv3 is an improved version of YOLOv2, featuring a new feature extraction network, a better backbone classifier, and multiscale prediction. Although Kumar et al [12] suggested a two-stage detector with high object detection accuracy, it is limited for video surveillance due to sluggish real-time inference speed. Although Morera et al [13] suggested YOLOv3, it achieved the same classification accuracy as a single-shot detector (SSD).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It aims to identify object instances in natural images from a wide range of predefined categories [6]. Object detection techniques are analyzed [7] to detect objects in real-time on any system running the proposed model in any area. The proposed method employs multi-layer convolutional neural networks to create a multi-layer system model that can classify given objects into specified classes.…”
Section: Related Workmentioning
confidence: 99%
“…In the object detection network without feature information fusion, one type of prediction is based on single-layer feature map, such as two-stage methods (Fast RCNN [16], Faster R-CNN [17]), single-stage methods YOLO (You Only Look Once) [18] and YOLOv2 [19]. The other is to predict on multiple feature graphs, such as SSD (single-shot multi-box detector) [20] and MS-CNN (multi-scale CNN) [21]. In the object detection network with feature information fusion, one kind of prediction is based on a single fused feature graph.…”
Section: Related Workmentioning
confidence: 99%